Audit Energi Untuk Pencapaian Penghematan Penggunaan Energi Pada Bangunan Gedung Perkantoran - Aprilia Putri Ningrum; Munawar Ali (Jurnal Universal Technic, 2024)
In line with the concept of environmentally friendly national development, every commercial and industrial activity must be committed to preserving the environment. This is in accordance with Law no. Regulation Number 32 of 2009 concerning Environmental Protection and Management. Referring to Law No.30 of 2007 concerning Energy, which was then followed up with Government Regulation No.33 of 2023 concerning Energy conservation which requires energy users above TOE to carry out Energy conservation by conducting periodic Energy Audits of Lighting Systems and Air Conditioning Systems . This research conducted an audit of lighting and air conditioning systems by collecting data on lighting intensity, temperature and humidity in each room in the office from 08.00 – 17.00 using a lux meter measuring instrument, then the results were analyzed by referring to the Indonesian National Standards (SNI) regarding lighting and Minister of Energy and Mineral Resources Regulation No. 13 of 2012 concerning Saving on Electricity Use. The use of electrical energy in the office work environment is still not optimal and even though the density value is satisfactory, the lighting level in the office still has rooms that do not meet SNI standards. Apart from that, the use of electrical energy for the air conditioning system is also considered insufficient so several recommendations need to be made